Sustainable Tourism Marketing - Marine-Roig, Estela (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
In this book, we introduce the themes and approaches covered in the issue Sustainable Tourism Marketing. Its objective was to analyze the main contributions made as a result of research related to sustainable tourism-marketing management and current trends in the field. This book gathered articles about the marketing of destinations, and the marketing and communication management of companies and tourism organizations from a sustainable tourism perspective.